VERIFYING OF THE HYPOTHESES AS FOR EXPENSES CAUSED BY ENTERPRISES ACTIVITY INFLUENCE ON ENVIRONMENT MODELING - Bartkova, Lyudmyla; Satkowiak, Frederick (International Journal of Computing, 2014)
How does industry effect on the environment cause health problems among the population? What levels of pollution affect the health of the population? Can the effects be measured, predicted, or controlled? Can the costs of health care be predicted based on ecological factors? Is there any correlation between the health of a population and environmental factors? The hypotheses as for the correlation between integrated ecological and social-economical factors and expenses caused by industry on environment are represented in the paper. The verifying of the hypotheses is illustrated by means of the concrete examples.